PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PBI DENGAN PENDEKATAN OPEN-ENDED DI SMP - Djadir, Djadir; Sahid, Sahid (Universitas Negeri Makassar, 2015)
This research is a kind of developmental research. The product of this research is a valid, practice, and effective mathematics learning package using open-ended approach in the topic of Linear Equation System with Two Variables. Specifically, the product comprehends of four components: Students’ book, Students’ worksheet, Lesson Plan, and Learning Outcome Test. The experiment was conducted in Grade VIII SMP Tanete Riaja in Barru. The results of the experiment are: (1) the developed mathematics learning package using open-ended approach is practice, however, as suggested by some observers, it could be improved still, then it can be more practice, (2) the developed mathematics learning package using open-ended approach is effective since it satisfies three of the four effectivity indicators. Based on the result of this research, it is suggested for those who will develop this research further to closely pay attention to the limitation of the research, so they can produce a better result. In addition, the kind of this development should be applied to other topics to make students interested, enjoy, and active in learning mathematics.